Entre sacralisation et insécurité : l’ambivalence du regard contemporain sur l’enfant - Gérard Neyrand (Éducation et Socialisation)
Early childhood has acquired much importance today. We might even talk of its social promotion, for a number of reasons: firstly, the transformation of our couple or family lifestyles; secondly, the recognition of the importance of early childhood for the future of society; thirdly, the diversification of the agents of its socialisation.